Reinhart Koselleck: His concept of the concept and neo-Kantianism - Palti, Elias Jose (2011)
The present article intends to trace the conceptual roots of Koselleck's concept of the concept. Koselleck's distinction between ideas and concepts has its roots in the logic of Hegel, who was the first to elaborate on the multivocal nature of concepts as their distinguishing feature vis-à-vis ideas. The main hypothesis proposed here is that Koselleck reformulated Hegel's view on the basis of the neo-Kantian philosophies developed at the turn of the century, with which his theory maintains a tense relationship, without breaking, however, some of its fundamental premises.